Pengaruh Konsumsi Minuman Jahe (Zingibers officinale) Saat Dismenore Pada Kalangan Remaja - Angel Novia Fransiska; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Ginger is a bioactive compound that has shogaol and gingerol compounds. Ginger has the activity inhibiting the enzymes cyclooxygenase and lipoxygenase from hormones. The effect of consuming ginger drinks is speedy, helping for 2-3 days after mass dysmenorrhea occurs; the relief of dysmenorrhea and giving ginger drinks is more effective for 72 hours. Dysmenorrhea is a symptom during menstruation that significantly interferes with daily activities. Dysmenorrhea can occur due to excessive hormone formation, which can cause faster contractions resulting in the narrowing of the blood lumen. Dysmenorrhea occurs from teenagers to adults. The aim of the effect of ginger drinks on dysmenorrhea is to provide adolescents with information on production health problems and the effects of consuming herbal drinks when dysmenorrhea occurs. Adolescents are the mass where puberty is from youth to adulthood. Adolescent mass often occurs from physical, psychological, and social changes. All adolescent changes are in the form of mind to the process of growing up to be productive with the first menstruation. I know the effect of ginger consumption during dysmenorrhea among adolescents by collecting several published journals from Google Scholar sources.